Optimization of injection moulding process using particle swarm optimisation algorithm through simulation student - Mohd Faisal Bin Mansur (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This paper describes the simulation work on how to reduce warpage in injection molding.Work simulation consists of three phases 'mold flow analysis, 'Response Surface Methodology, Particle Swarm Optimisatiom.